Klatskin Tumor: A Survival Analysis According to Tumor Characteristics and Inflammatory Ratios - Vlad-Ionuţ Nechita; Emil Moiş; Luminiţa Furcea; Mihaela-Ancuţa Nechita; Florin Graur (Medicina, 2022)
Background and Objectives: The aim was to evaluate the association of inflammatory biomarkers with resectability and overall survival in hilar cholangiocarcinoma. Materials and Methods: We conducted a retrospective cohort study over 72 consecutive surgical cases of Klatskin tumor over an 11-year period. The sample was divided into two groups: 42 surgical resection cases and 30 unresectable tumors. Values of inflammatory ratios were compared according to the resectability. Log-rank test, univariate, and multivariate Cox proportional hazards models were used to evaluate the overall survival. Results: Subjects were between 42–87 years old (average age of 64.91 ± 9.15 years). According to the procedure: 58.33% benefited from resection (with a 30.95% R0 resection rate) and 41.66% had palliative surgery. Elevated NLR (neutrophil to lymphocyte ratio), PLR (platelet to lymphocyte ratio), and SII (systemic immune-inflammation index), and lower LMR (lymphocyte to monocyte ratio) at admission were associated with unresectable tumors (p < 0.01). For the multivariate Cox proportional hazard models, increased absolute values of NLR, PLR, and SII were associated with lower survival; no differences were observed for LMR absolute value. The cut-off value of NLR ≥ 6 was associated with lower survival. The median survival time for all subjects was 442 days, with 774 days for the resection group and 147 days for the group with palliative surgery. Conclusions: In hilar cholangiocarcinoma, inflammatory ratios are associated with tumor resectability. Tumor excision conferred an important advantage in survival. Elevated NLR, PLR, and SII values at admission significantly increased the hazard ratio. LMR had no influence on survival.